Heterogeneous Effects of High School Peers on Educational Outcomes - Silvia Mendolia; Alfredo R. Paloyo; Ian Walker (Institute for the Study of Labor (IZA), 2016)
We investigate the relationship between peers' abilities and educational outcomes at the end of high school using data from the rich Longitudinal Study of Young People in England (LSYPE) matched to the National Pupil Database of children in state schools in England. In particular, we focus on the effect of peers' abilities, measured through achievements in Key Stage 3 (Age 14), on high powered test scores at Ages 16 and 18, and on the probability of attending university. Our identification strategy is based on a measure of the peers of peers' ability. In particular, for each individual, we look at her high school peers and select their primary school peers who do not attend the same high school and who did not attend the same primary school as the individual. We then use peers-of-peers ability, measured using Age 11 test scores as an instrument for high school average peer ability, measured using Age 14 test scores. We also use quantile regression to explore the effect of peers' ability on different parts of the distributions of the outcomes. Our results show that average of peers' abilities has a moderate positive effect on test scores at Ages 16 and 18, and that being in a school with a large proportion of low-quality peers can have a significantly detrimental effect on individual achievements. Furthermore, peers' ability seems to have a stronger effect on students at the bottom of the grade distribution, especially at Age 16.
Keywords: I20; J24; 330; peer effects; instrumental variables; test scores